PENERAPAN DIGITAL MARKETING PADA UMKM FATRIOSAL MAIN KAYU - Sihombing, Agustinus; Fatahuddin, Fatahuddin; Mu’azamsyah, Muhammad (P3M STIE Pembangunan Tanjungpinang, 2024)
This service aims to educate and socialize MSME players about the application of digital marketing in improving the MSME economy during the Covid 19 pandemic. This service was carried out at Fatriosal Kayu Utama MSME which is located on Jl. Darussalam Gg. Kenanga 2 RT 02 RW 04 Bukit Cermin Village. UMKM Fatriosal Kayu Utama was founded in 2018, even though it has been around for a long time, this business has not shown great development. This is because Fatriosal Main Kayu MSMEs have several limitations, such as the main raw materials for production which are difficult to find in Tanjungpinang City, limited production tools, lack of knowledge about marketing strategies in the digital world, lack of recognition of market places and digital literacy. To solve this problem, our group in this service activity will run the programs, namely: a) digital marketing strategy; b) know the market place, accessibility, types and features; and c) the role of digital literacy in the world market. The methods we use in implementing the program consist of socialization, interviews and practice methods